Zero net energy education: mind the gap - Kwok, Alison G; Tepfer, Sara; Grondzik, Walter T (ARCC Conference Repository, 2014)
Seven years after the American Institute of Architect's adoption of the 2030 Challenge, 233 architecture firms across the nation have committed to reducing energy consumption by 60% (from a baseline national average) before the year 2030. Simultaneously, 86% of A/E firms report difficulty finding employees equipped with the knowledge and skills necessary to achieve this goal. Such a gap between supply and demand begs the question: is architectural education rising to the challenge of effectively communicating energy-efficient design strategies? This paper presents a follow-up study examining the state of zero-net-energy (ZNE) education in accredited architecture schools across North America. Previous work relied upon statistical analysis of 45 syllabi for foundational building science courses; these were self-reported from instructors from 29 accredited institutions. The study showed that these instructors were dedicating approximately 25% of course time to ZNE-related topics through a combination of lecture- and project-based learning. While insightful, the limitations of the statistical methodology and narrow information from the syllabi left many questions unanswered. The study presented here in builds upon the previous work, to first re-examine thesyllabi under a different lens and also to look beyond the documents to what the instructors say. Targeted surveys were used to uncover stories that cannot be easily identified through syllabus review and to reveal how "sustainable” design education is [or isn't] being handled. We hypothesized that architectural curricula have tremendous inertia, and we (faculty) are lagging in adequately preparing students for the challenges of the present and future. Survey responses revealed that fundamentals of environmental controls were being taught, but specific ZNE applications were not. Faculty perceived that students were moderately prepared to meet the 2030 Challenge. Institutional demographics revealed that environmental controls are typically taught in the third year for undergraduates and in the first year for graduate students.